Sharia Arbitration as an Alternative Settlement of Sharia Banking Disputes - Muhamad Kholid (International Journal of Nusantara Islam, 2018)
The enactment of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking, became an explicit formal juridical basis for the implementation of the Islamic banking system in Indonesia. These developments should be accompanied by anticipatory steps regarding the problem of settling the dispute. Law Number 30 of 1999 concerning Arbitration and APS (Alternative Dispute Settlement) responds to existing deficiencies by preparing dispute resolution institutions through arbitration. The type of arbitration authorized to settle Islamic banking in Indonesia is Sharia Arbitration so that Sharia Arbitration is the main choice for Sharia Banking business actors. This article will discuss the authority and effectiveness of Sharia Arbitration decisions in resolving Islamic banking disputes in Indonesia. The method used is normative juridical. The study was conducted with 2 (two) stages, namely: library research (library research) and field research (field research). Data collection is done by document study and interview. Data Analysis Method used is descriptive analytical with qualitative normative juridical approach. The results of the study concluded that Sharia Arbitration competencies can resolve sharia banking disputes which are part of the Islamic economy coupled with disputes which according to the law can be held peace.